2019
DOI: 10.1107/s205979831901074x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-ligand variants of the myocilin olfactomedin propeller selected from invertebrate phyla reveal cross-talk with N-terminal blade and surface helices

Abstract: Olfactomedins are a family of modular proteins found in multicellular organisms that all contain five-bladed β-propeller olfactomedin (OLF) domains. In support of differential functions for the OLF propeller, the available crystal structures reveal that only some OLF domains harbor an internal calcium-binding site with ligands derived from a triad of residues. For the myocilin OLF domain (myoc-OLF), ablation of the ion-binding site (triad Asp, Asn, Asp) by altering the coordinating residues affects the stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A starting point for evaluating the consequences of OLF mutations in the absence of other data would be based on their likelihood of affecting one of the aforementioned main structural features of the OLF domain. In general, though not always (Hill, Cho, et al, 2019; Hill, Kwon, et al, 2019), structure‐based physicochemical intuition provides a rationale for a deleterious prediction. For example, modifications to surface loops lacking discrete intermolecular interactions with other residues in the domain are likely to tolerate mutations more readily than changes internal to the structure where the substitution interferes with the native packing and intermolecular interactions.…”
Section: Structural Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A starting point for evaluating the consequences of OLF mutations in the absence of other data would be based on their likelihood of affecting one of the aforementioned main structural features of the OLF domain. In general, though not always (Hill, Cho, et al, 2019; Hill, Kwon, et al, 2019), structure‐based physicochemical intuition provides a rationale for a deleterious prediction. For example, modifications to surface loops lacking discrete intermolecular interactions with other residues in the domain are likely to tolerate mutations more readily than changes internal to the structure where the substitution interferes with the native packing and intermolecular interactions.…”
Section: Structural Datamentioning
confidence: 99%
“…Based on this observation, the substitution of residues found on the interior of the OLF propeller would be expected to be poorly tolerated. Unexpectedly, we increased OLF stability by introducing single or double‐point variants at relatively conserved internal positions corresponding to calcium ligands, which should not have been tolerated (Hill, Cho, et al, 2019; Hill, Kwon, et al, 2019). One variant we did not study in the lab but has clinically been found only in control subjects, N428S, may be similarly stabilizing, or perhaps additional functional insights will reveal a loss of function relevant to glaucoma.…”
Section: The Complex Structure‐misfolding Relationship For Olf Missense Variantsmentioning
confidence: 99%
“…The side helix that sits between blades E and A, which likewise remains unassigned, may also be somewhat unwound based on our structures of metal ligand variants (Supplementary Fig. 11 ) but this can happen without introducing thermal destabilization characteristic of aggregation-prone disease variants 27 , 42 . Overall, we deduce that perturbations yielding destabilized, aggregation-prone OLF are distinct from what is observed for stable variants that do not aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we established that disease variants within OLF were thermally destabilized ( Burns et al, 2011 ) and exhibited non-native structural signatures in solution ( Hill et al, 2014 ); the other structural domain of myocilin, a coiled coil, does not aggregate and has a T m ∼15°C higher than OLF (67°C; Hill et al, 2017 ). However, OLF can tolerate particular variations ( Hill et al, 2019a ; Hill et al, 2019b ), including some that lead to pronounced structural deviations ( Hill et al, 2019b ), without pathogenic signatures. For example, the D478S point mutation is thermally tolerated even though it ablates calcium binding, shifts an entire β-propeller blade by 0.5 Å and disorders the side helix ( Fig.…”
Section: Discussionmentioning
confidence: 99%